2014
DOI: 10.1007/s12072-014-9559-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of patients’ knowledge about hepatitis C in the United States and in urban and rural China

Abstract: Knowledge about HCV in the US and Beijing patients was similar and significantly better than in Hebei patients. Our data show that efforts to improve HCV knowledge are necessary for all three cohorts and should be tailored to the education level and health literacy of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…After adjusting for all other potential confounders in the logistic regression model, education level, occupation, and annual household income were factors associated with a prevalence of low health literacy. Our findings were consistent with several large-scale surveys of adult health literacy, which reported that the most common socio-demographic features associated with health literacy were education level, age, ethnicity, geographic location, and income [8,22,23,24,25,26,27,28]. Our study demonstrated that, after adjusting for potential confounders, the prevalence of low health literacy was significantly associated with occupation, education level, and annual household income.…”
Section: Discussionsupporting
confidence: 91%
“…After adjusting for all other potential confounders in the logistic regression model, education level, occupation, and annual household income were factors associated with a prevalence of low health literacy. Our findings were consistent with several large-scale surveys of adult health literacy, which reported that the most common socio-demographic features associated with health literacy were education level, age, ethnicity, geographic location, and income [8,22,23,24,25,26,27,28]. Our study demonstrated that, after adjusting for potential confounders, the prevalence of low health literacy was significantly associated with occupation, education level, and annual household income.…”
Section: Discussionsupporting
confidence: 91%
“…Health literacy is defined by the ability of individuals to acquire, analyze, and understand the information and basic health services that they need to make the right decisions about their health issues. If the health literacy of HCV patients is appropriate, the ability to understand and then to put into practice medical advice of health professionals is higher, favoring the process of adherence to treatment …”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained by the fact that patients with HCV seek to acquire knowledge about the disease after being diagnosed. Previous research has also shown that patients from the United States and China have good knowledge of HCV (WU et al, 2015), however, permanent health education must be way to improve the knowledge level of patients and the population general about viral hepatitis .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies about HCV knowledge have been conducted among patients with chronic HCV infection (MARCHESINI et al, 2007;SHAH;ABU-AMARA, 2013;WU et al, 2015). Therefore, to the best of our knowledge, the aim of this study was to evaluated the knowledge about viral transmission among HCV infected individuals and attitudes regarding toothbrush care.…”
Section: Introductionmentioning
confidence: 97%